Vehicle and Automotive Engineering 2 Proceedings of the 2nd VAE2018, Miskolc, Hungary (Lecture Notes in Mechanical Engineering,, 2018)
This book presents the proceedings of the second Vehicle Engineering and Vehicle Industry conference, reflecting the outcomes of theoretical and practical studies and outlining future development trends in a broad field of automotive research. The conference's main themes included design, manufacturing, economic and educational topics.